Use of the PCR technique to diagnose meningitis in children admitted to Red Cross War Memorial Children’s Hospital - Mteshana, Phindile (Department of Paediatrics and Child Health, 2019)
Introduction: Viral meningitis (VM) is more common than bacterial meningitis (BM) and is a self-limiting disease. Clinicians still tend to admit patients with VM and treat them for BM because they fear the morbidity and mortality that is associated with a delay in treating or not treating BM. Unnecessary admissions have huge cost implications and they separate children from their parents while exposing them to painful procedures and unnecessary antibiotics. Methods: A structured literature review was undertaken to see whether clinical manifestation and examination findings and laboratory findings including viral PCR of cerebrospinal fluid can help to diagnose viral meningitis and avoid unnecessary admissions.